2013
DOI: 10.1016/s2221-1691(13)60068-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary schistosomiasis and malaria associated anemia in Ethiopia

Abstract: The study showed that anemia is higher in concurrently infected children than non-infected and single infected. Furthermore, level of hemoglobin was negatively correlated with the number of S. haematobium eggs and malaria parsitemia. Therefore, examination of hemoglobin status in patients co-infected with malaria and schistosomiasis is important to reduce the risk of anemia and to improve health of the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 17 publications
6
50
5
Order By: Relevance
“…Several studies including Casmo et al [28] and Deribew et al [29] have establish an association between the intensity of Schistosoma egg count and Hb concentration in similar studies. The study by Deribew et al in Ethiopia for example, found a significantly negative correlation between egg count/intensity and haemoglobin concentration.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies including Casmo et al [28] and Deribew et al [29] have establish an association between the intensity of Schistosoma egg count and Hb concentration in similar studies. The study by Deribew et al in Ethiopia for example, found a significantly negative correlation between egg count/intensity and haemoglobin concentration.…”
Section: Discussionmentioning
confidence: 60%
“…falciparum infection (Fig 2). A cross-sectional study in Ethiopia [31] and a prospective cohort study in Mali [36] showed increased odds of asymptomatic/uncomplicated P . falciparum infection among children infected with S .…”
Section: Resultsmentioning
confidence: 99%
“…haematobium than those uninfected with S . haematobium (summary OR: 1.68; 95%CI: 1.18, 2.41; I 2 : 53.2%) [31,32, 3436, 38]. However, longitudinal studies in Mali showed similar risk of uncomplicated P .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schistosomiasis is a major parasitic disease of the tropics, causing acute and long-term clinical syndromes (1) (2) . Among schistosomicidal drugs, praziquantel is the drug of choice in most areas of endemicity owing to its superior effi cacy (3) .…”
Section: Introductionmentioning
confidence: 99%